2017
DOI: 10.3390/nu9070772
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Red Ginseng on Genotoxicity and Health-Related Quality of Life after Adjuvant Chemotherapy in Patients with Epithelial Ovarian Cancer: A Randomized, Double Blind, Placebo-Controlled Trial

Abstract: We evaluated the effect of red ginseng on toxicity, health-related quality of life (HRQL) and survival after adjuvant chemotherapy in patients with epithelial ovarian cancer (EOC). A total of 30 patients with EOC were randomly assigned to placebo (n = 15) and red ginseng groups (n = 15). All patients took placebo or red ginseng (3000 mg/day) for three months. Then, we compared changes of genotoxicity, HRQL and survival between the two groups. As a result, red ginseng reduced micronuclei yield in comparison wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 47 publications
3
42
0
1
Order By: Relevance
“…Its anticancer mechanisms mainly include cell cycle arrest, apoptosis/paraptosis induction, and angiogenesis inhibition (Wang et al, 2016 ). Recently, a randomized double blind placebo-controlled trial demonstrates that Red Ginseng decreases symptom of nausea, vomiting, dyspnea and fatigue, and its efficacy and safety can improve life quality in patients receiving six cycles of adjuvant taxane- and platinum-based chemotherapy after cytoreductive surgery (Kim H. S. et al, 2017 ). A phase II randomized double-blind placebo-controlled study shows that safe and well-tolerated 6-gingerol improves the overall complete response rate in nausea and vomiting, appetite as well as quality of life in cancer patients with surgical resection of primary tumor and moderately to highly emetogenic adjuvant chemotherapy (Konmun et al, 2017 ), further demonstrating that ginger supplementation can significantly reduce the severity of chemotherapy-induced nausea in adult cancer patients (Ryan et al, 2012 ).…”
Section: Mitigation Of Gastrointestinal Toxicity By Regulating Gastromentioning
confidence: 99%
“…Its anticancer mechanisms mainly include cell cycle arrest, apoptosis/paraptosis induction, and angiogenesis inhibition (Wang et al, 2016 ). Recently, a randomized double blind placebo-controlled trial demonstrates that Red Ginseng decreases symptom of nausea, vomiting, dyspnea and fatigue, and its efficacy and safety can improve life quality in patients receiving six cycles of adjuvant taxane- and platinum-based chemotherapy after cytoreductive surgery (Kim H. S. et al, 2017 ). A phase II randomized double-blind placebo-controlled study shows that safe and well-tolerated 6-gingerol improves the overall complete response rate in nausea and vomiting, appetite as well as quality of life in cancer patients with surgical resection of primary tumor and moderately to highly emetogenic adjuvant chemotherapy (Konmun et al, 2017 ), further demonstrating that ginger supplementation can significantly reduce the severity of chemotherapy-induced nausea in adult cancer patients (Ryan et al, 2012 ).…”
Section: Mitigation Of Gastrointestinal Toxicity By Regulating Gastromentioning
confidence: 99%
“…In a more recent randomized, double-blinded, placebo-controlled trial, 30 patients with epithelial ovarian cancer in Korea were given placebo or red ginseng (3000 mg/day) for three months. The results suggested that red ginseng may be capable of decreasing genotoxicity and enhancing health-related quality of life despite no benefit of survival in patients with epithelial ovarian cancer who received chemotherapy [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng is one of the herbs that proved to be beneficial for the treatment. According to many studies, ginseng is active in maintaining health and effective in the prevention and treatment of cancers by different mechanisms ( 23 25 ). Ginseng is not only effective in reducing chemotherapy side effects and improving the quality of patient's life, it also plays a crucial role in inflammation reduction and thereby reduces the risk of cancer ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%